Observational multicenter study of efficacy of paroxetine filmcoated tablet in the treatment of anxiety disorder - Alma Džubur Kulenović; Amra Memić Serdarević; Zehra Halilović; Haris Mašnić; Amra Bahto; Belma Kapo; Daniela Delić; Amila Hadžimuratović (Medicinski glasnik, 2018)
Aim: To examine the efficiency of paroxetine treatment of anxiety disorders in adult patients over the period of 12 months and the improvement of symptoms of anxiety disorder during this period, as well as to examine the tolerability of the administered treatment and patient compliance during the study. Methods: This observational, multicenter, cohort, clinical study included 171 patients with diagnosed anxiety disorder who were administrated paroxetine film-coated tablets 20 mg and followed up during the next 12 months. Patients were observed at 6 points, baseline and five additional assessments. The Beck Anxiety Inventory was used to determine the baseline severity of anxiety and Patients Health Questionnaire module GAD-7 was used to determine the severity of anxious symptoms and to follow up patients during the additional observations. Tolerability and patient compliance were followed throughout the study. Results: Statistically significant decline in severity of anxiety disorder over the observation period (p=0.001) was found. At the beginning of the study, 64 (45.7%) patients had severe anxiety symptoms, 43 (30.7%) moderate, 25 (17.9%) mild and eight (5.7%) had none to minimal symptoms. At the end of the study, there were no more patients with severe anxiety, while four (3.4%) had moderate symptoms. On the other hand, 26 (22.2%) had mild symptoms and 87 (74.4%) had none to minimal symptoms of anxiety disorder. Conclusion: The results of this study provide further evidence for paroxetine's efficacy and tolerability in the treatment of anxiety disorders with good patient compliance.
Keywords: anxiety disorder; drug tolerance; treatment outcome; paroxetine